Screening Program for Idiopathic Scoliosis by Adam’s Bending Forward Test of Prepubertal Children at Primary Schools in Baghdad City - Saleh, Buthainah; Ma΄ala Eqbal (Iraqi National Journal of Nursing Specialties, 2014)
Objective: The study aimed to screen the prepubertal children for idiopathic scoliosis at earlier stages, and find out the relationship between idiopathic scoliosis and demographic data such as age, sex, body mass index, heavy backpacks, and heart & lung diseases. Methodology: A descriptive study was conducted on screening program for prepubertal children in primary schools at Baghdad city, starting from 24th of February to the end of October 2010. Non- probability (purposive) sample of 510 prepubertal children were chosen from primary schools of both sides of Al-Karkh and Al-Russafa sectors. Data was collected through a specially constructed questionnaire format include (24) items multiple choice questions, and researcher observation. The validity of the questionnaire was determined through a panel of experts related to the field of the study, and the reliability through a pilot study. The data were analyzed through the application of descriptive statistical analysis frequency, & percentages, and inferential statistical analysis, chi-square, are used. Results: The study results revealed that most of the prepubertal children have idiopathic scoliosis, two third of the sample (88.4%) were at age 10-12 years and mostly boys. There is highly significant association with (low Body Mass Index & carry of the school backpack) but no significant association with the age, gender, and lung & heart diseases. There is highly significant association between prepubertal children’s idiopathic scoliosis signs & the researcher observation for the prepubertal body feature, and Adam’s Bending Forward Test which revealed highly significant association with their idiopathic scoliosis. The results of the study reflect that the majority of prepubertal children’s idiopathic scoliosis deformities have significant association at early detection than the other spinal deformities (kyphosis & kyphoscoliosis). Recommendation: The researchers recommended that Ministry Of Health should activate the screening program of scoliosis within school health service programs, and Ministry of Education should be involved their teachers in the screening & training program.